IDENTIFIKASI KANDUNGAN MERKURI (Hg) PADA KRIM PEMUTIH WAJAH YANG DIJUAL DI PASAR ANDIR DENGAN METODE SPEKTROFOTOMETRI SERAPAN ATOM (SSA) - Ani Haerani; Suci Rizki Nurul Aeni; Sapta Nisa Andini (Pharma Xplore : Jurnal Sains dan Ilmu Farmasi, 2022)
Cosmetics are materials or preparations intended for use on the outside of the human body, one of which is facial whitening cream. Face whitening cream is part of cosmetics that contains a mixture of chemicals that are efficacious to reduce skin hyperpigmentation so that the skin looks brighter. One of the ingredients that should not be used in facial whitening creams is mercury. The addition of mercury in facial whitening creams has been prohibited if it exceeds 1mg/kg because it is very dangerous. Mercury content in facial whitening cream can be analyzed using Atomic Absorption Spectrophotometry (AAS). The purpose of the study was to determine the mercury (Hg) and mercury (Hg) levels in facial whitening creams circulating in the Pasar Andir area of ​​Bandung. Research Methods: This study used a descriptive method. knowing the description of mercury (Hg) levels in whitening cream circulating in the Andir Bandung market area using the Atomic Absorption Spectrophotometer (AAS) method. Based on the research results from eleven samples of whitening cream, 5 samples of whitening cream were positive for mercury and 6 samples were negative for mercury. In sample 001 obtained mercury levels of (0.05 mg/Kg), sample 005 (1361.50 mg/Kg), sample 006 (0.43 mg/Kg), sample 007 (0.02 mg/Kg), sample 010 (0.12 mg/Kg), and samples that did not contain mercury were found in samples 002, 003, 004, 008, 009 and 011, namely 1mg/Kg, namely (< 0.005 mg/Kg). Sample 005 contained 1361.50 mg/Kg of Mercury, so the cream sample did not meet the requirements for distribution according to the provisions of the Head of the BPOM.